Hip sublime : Beat writers and the classical tradition - Murnaghan, Sheila, 1951-; Rosen, Ralph Mark (Classical memories/modern identities., 2018)
"With essays that cover canonical Beat authors such as Allen Ginsberg, Jack Kerouac, and William Burroughs as well as less well-known figures like Kenneth Rexroth, Ed Sanders, and Diane di Prima, this volume focuses on the Beat movement's appropriation of the Greek and Latin classics as a formative element of their literary movement"--